Some problems for multidimensional integro-differential equations of hyperbolic type - Aldashev, S. A. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We prove the well-posedness of the Cauchy, Goursat, and Darboux problems for multidimensional in-tegro-differential equations of the hyperbolic type encountered in biology.